The Conditional CAPM and the Cross‐Section of Expected Returns - JAGANNATHAN, RAVI; WANG, ZHENYU (Journal of Finance, 1996)
ABSTRACT Most empirical studies of the static CAPM assume that betas remain constant over time and that the return on the value‐weighted portfolio of all stocks is a proxy for the return on aggregate wealth. The general consensus is that the static CAPM is unable to explain satisfactorily the cross‐section of average returns on stocks. We assume that the CAPM holds in a conditional sense, i.e., betas and the market risk premium vary over time. We include the return on human capital when measuring the return on aggregate wealth. Our specification performs well in explaining the cross‐section of average returns.